Proceedings of the 35th Annual Computer Security Applications Conference 2019
DOI: 10.1145/3359789.3359811
|View full text |Cite
|
Sign up to set email alerts
|

Co-evaluation of pattern matching algorithms on IoT devices with embedded GPUs

Abstract: Pattern matching is an important building block for many security applications, including Network Intrusion Detection Systems (NIDS). As NIDS grow in functionality and complexity, the time overhead and energy consumption of pattern matching become a significant consideration that limits the deployability of such systems, especially on resource-constrained devices. On the other hand, the emergence of new computing platforms, such as embedded devices with integrated, general-purpose Graphics Processing Units (GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…However, with the increasing complexity and functionality of NIDS, pattern matching requires more time and energy consumption. Stylianopoulos et al [90] proposed a new pattern matching architecture, which brings new and exciting opportunities for algorithm design, based on embedded GPUs. They evaluated the algorithms on a heterogeneous device and found that GPU-based pattern matching algorithms have competitive performance compared to a CPU and consume half as much energy as the CPU-based variants.…”
Section: Anomaly Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the increasing complexity and functionality of NIDS, pattern matching requires more time and energy consumption. Stylianopoulos et al [90] proposed a new pattern matching architecture, which brings new and exciting opportunities for algorithm design, based on embedded GPUs. They evaluated the algorithms on a heterogeneous device and found that GPU-based pattern matching algorithms have competitive performance compared to a CPU and consume half as much energy as the CPU-based variants.…”
Section: Anomaly Detectionmentioning
confidence: 99%
“…Typically, rule-based matching is the easiest and fastest way to detect attacks, but it cannot adapt to new attack models. Recent studies have attempted to solve this problem with new approaches, such as behavior-rule specification-based techniques [17], artificial neural networks (ANNs) [89], pattern matching accelerated by GPUs [90], and model-checking [91]. Moreover, they also leveraged fingerprinting techniques to enhance the intrusion detection scheme [11], as minor differences in devices can be used to identify spoofed command responses.…”
Section: Network Layermentioning
confidence: 99%
“…They range from operating system interrupts or scheduling and timesharing with other tasks. Moreover, the packet processing application itself needs to be optimized to make best use of the underlying hardware [23] and focus on delivering low latency. Hence, the performance and feasibility of using commodity hardware for latency-critical event-based applications is still an open issue.…”
Section: Introductionmentioning
confidence: 99%